The Study of Labour, Employment, and Work Life: Central Features and Core Principle - Kaufman, Bruce E (Arbetsmarknad & Arbetsliv, 2018)
The multi-disciplinary study of labour, employment and work life (LEWL) has a long history and is conducted in universities and research organizations across the world. In English-speaking countries LEWL is typically named “industrial relations” (or “employment relations”), while in Sweden the typical name is “arbetsmarknads- och arbetslivsforskning.” Regardless of differences in labels and organizational structures, the LEWL field has certain common ideas and principles across all countries that give it a concrete identity and position in the social sciences. In this paper I identify these common features and the central intellectual principle that distinguishes LEWL from its major competitor, orthodox (neoclassical) economics. I also identify reasons why the LEWL field is declining in many countries, symbolized in Sweden by the closing of the National Institute for Work Life.